Pengaruh Lokasi Geografis dan Vegetasi terhadap Sifat Fisikokimia Madu dari Ciwidey dan Bogor - Emanuela Rae Alodia; Anas Bunyamin; Efri Mardawati (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2020)
Physicochemical properties are one of the parameters of honey quality that impacts the sales of honey as well as the economy condition of the society in Ciwidey and Bogor. The physicochemical properties of honey are significantly influenced by the origin of the honey, including its geographical location and vegetation. This study aims to determine the physicochemical properties between multiflora honey from Ciwidey and Bogor with different source of nectar where Ciwidey honey is dominated by calliandra nectar while Bogor honey is dominated by kapok nectar. Data were analyzed with descriptive and quantitative method using independent t test for data with normal distribution (water content and reducing sugar content). Data that were not normally distributed (color analysis and acidity value) were tested non-parametrically with the Mann Whitney-U. The results showed that Bogor honey has the better physicochemical properties and meets Indonesian National Standard (Standar Nasional Indonesia, SNI) 8664:2018, with a water content of 15.15% w/w, L* values of 35.26, a* value of 28.66, b* value of 59.46, c* value of 66.01, h* value of 64.27°, reducing sugar content of 78.78% and acidity value of 35.56 mL NaOH kg-1. Phytochemical screening showed positive results on alkaloid, flavonoid, phenol and tannin, and the results of GC-MS analysis showed three significant compounds which are hydroxymethylfurfural of 48.26%, levoglucosan of 13.58% and ammonium carbamate of 9.18%.